1992
DOI: 10.1128/jb.174.20.6359-6367.1992
|View full text |Cite
|
Sign up to set email alerts
|

vacB, a novel chromosomal gene required for expression of virulence genes on the large plasmid of Shigella flexneri

Abstract: Shigellae, the causative agents of bacillary dysentery, are capable of adhering to and invading epithelial cells and spreading into adjacent cells. A chromosomal mutant of ShigeUla flexneri 2a YSH6000 with reduced invasive capacity was isolated by TnS insertion mutagenesis. The linkage of the mutant phenotype to the TnS insertion was determined by P1 phage transduction. The site of the TnS insertion was assigned to a NotI chromosomal restriction map, confirming that the virulence-associated locus, designated v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 36 publications
3
97
0
Order By: Relevance
“…11). The results are in agreement with what has been reported for Shigella flexneri and E. coli EIEC, in which the ⌬rnr mutant strains were shown to be less invasive (50). These results indicate that RNase R, similarly to what was shown for polynucleotide phosphorylase (10), is an important protein for the first steps of infection of C. jejuni.…”
Section: ϩsupporting
confidence: 82%
“…11). The results are in agreement with what has been reported for Shigella flexneri and E. coli EIEC, in which the ⌬rnr mutant strains were shown to be less invasive (50). These results indicate that RNase R, similarly to what was shown for polynucleotide phosphorylase (10), is an important protein for the first steps of infection of C. jejuni.…”
Section: ϩsupporting
confidence: 82%
“…In a transposon mutagenesis screen, a Shigella flexneri was isolated that displayed reduced host cell invasion. The disruption was mapped to a locus that was later identified as the gene (vacB/rnr) encoding RNaseR (27,28). More pertinent to this study and as mentioned in the introduction, a pnp mutant of Salmonella enterica was found to have a disregulated TTSS (12).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, RNase R plays an important role in degradation of mRNAs with extensive secondary structures (Chen and Deutscher 2005) and in the quality control of rRNA and tRNA Deutscher 2002, 2003;Li et al 2002;S Chebolu, C Kim, E Quesada, and MP Deutscher, unpubl.). RNase R is also required for the expression of virulence genes in Shigella and enteroinvasive strains of E. coli (Tobe et al 1992). It also associates with the tmRNASmpB complex, which releases stalled ribosomes via a process known as trans-translation (Karzai and Sauer 2001;Withey and Friedman 2003).…”
Section: Introductionmentioning
confidence: 99%